Primary Diffuse Large B-Cell Lymphoma of the Urinary Tract: A Population-Based Analysis - Liu, Zheng-Huan; Yang, Lu-Chen; Song, Pan; Fang, Kun; Zhou, Jing; Peng, Zhu-Feng; Dong, Qiang (Frontiers in Oncology, 2021)
Objective Diffuse large B-cell lymphoma (DLBCL) is the most common histopathological type of non-Hodgkin’s lymphoma, which may arise from various extranodal sites. Little is known about the clinical characteristics and survival outcomes of primary DLBCL of the urinary tract (UT). Thus, we conducted this study to explore the independent prognostic factors of patients with UT-DLBCL using the Surveillance, Epidemiology, and End Results (SEER) database. Materials and Methods We searched the Surveillance, Epidemiology, and End Results (SEER) database for the data of patients diagnosed with UT-DLBCL between 1975 and 2016. Data, including demographic tumour stage and therapeutic strategies, such as surgical resection, radiation therapy, and chemotherapy, were collected. The impact of these factors on survival outcomes, including overall survival (OS) and disease-specific survival (DSS), was analysed using Kaplan–Meier curves. Results Four-hundred and eighty-nine patients who met the inclusion criteria were enrolled in the data analysis. The median age was 69 years old. Most cases of UT-DLBCL (72.39%) originated from the kidney, followed by the urinary bladder (24.95%). Both surgical resection and chemotherapy can significantly improve OS and DSS. Patients older than 75 years had the worst survival outcomes. Stage IV DLBCL may be a poor prognostic factor. Conclusion To the best of our knowledge, this is the largest population-based study of UT-DLBCL. Advanced age, male gender, lack of surgical resection or chemotherapy, and stage IV DLBCL were poor prognostic factors.